Effects of Pb(II) on the flotation behaviour of galena with sodium humate as depressant. (October 2022) - Cui, Yanfang; Jiao, Fen; Qin, Wenqing; Yang, Congren; Wang, Xu; Li, Wei; Zhang, Zhengquan; Li, Xinchun
Highlights: Pb 2+ could greatly enhance the depression effect of sodium humate. Pb 2+ improved the adsorption of sodium humate onto the galena surface. At pH < 9.4, Pb 2+ and PbOH + could provide adsorption sites for NaHA. At pH > 9.4, Pb(OH)2(aq) and Pb(OH) 3- could not provide adsorption sites for NaHA. An adsorption model are finally obtained. Abstract: In this study, the effect of Pb 2+ on the flotation behaviour of galena using sodium humate (NaHA) as a depressant was investigated through micro-flotation tests, contact angle measurements, FTIR analysis, ICP tests and atomic force microscopic measurements. The micro-flotation test illustrated that Pb 2+ could greatly enhance the depression effect of NaHA and reduce the amount of NaHA. Mechanism studies showed that Pb 2+ improved the adsorption of NaHA onto the galena surface or reacted with NaHA in the solution to form the complexes of Pb 2+ and NaHA, thus improving the depression effect of NaHA for galena. At pH < 9.4, Pb 2+ and PbOH + could provide adsorption sites for NaHA. Therefore, the recovery of galena was <10 %. However, at pH > 9.4, Pb(OH)2(aq) and Pb(OH)3 − could not provide adsorption sites for NaHA. Therefore, the recovery of galena increased.